1995
DOI: 10.1080/10601329508019186
|View full text |Cite
|
Sign up to set email alerts
|

Novel Copolymers of Trisubstituted Ethylenes with Styrene. II. Halogen Ring-Substituted Methyl 2-Cyano-3-Phenyl-2-Propenoates

Abstract: Electrophilic trisubstituted ethylene monomers, ring-substituted methyl 2-cyano-3-phenyl-2-propenoates, RC6H4CH = C(CNC02CH, (where R is 0-C1, m-C1, p-C1, p-Br, and p-F) were prepared and copolymerized in solution with styrene at equimolar monomer feed composition in the presence of a radical initiator, AIBN at 80°C. The order of reactivity (lh,) for the trisubstituted ethylene monomers was p-C1 (3.0) > m-CI (2.9) > p-Br (2.3) > 0-C1 (2.0) > p-F (1.4). High Tg's of the copolymers in comparison with that of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The preparation procedure and characterization of the TSE monomers was described earlier [9,10]. The condensation reaction proceeded smoothly, yielding crystalline products, which were purified by conventional techniques.…”
Section: Synthesis Of the Tse Monomersmentioning
confidence: 99%
“…The preparation procedure and characterization of the TSE monomers was described earlier [9,10]. The condensation reaction proceeded smoothly, yielding crystalline products, which were purified by conventional techniques.…”
Section: Synthesis Of the Tse Monomersmentioning
confidence: 99%
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 17.2 and 29.6 mol% of MEPA is present in the copolymers prepared at ST/MEPA = 3 (mol), which is indicative of relatively high reactivity of the MEPA monomers towards ST radical which is typical of phenoxy ring-substituted phenylcyanoacrylates [18][19][20][21][22][23][24]. Since MEPA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated MEPA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Mepa Copolymersmentioning
confidence: 95%
“…Earlier we have reported synthesis and styrene copolymerization a number of halogen ring-substituted PCAs, such esters as methyl [18][19], ethyl [20], propyl [21], isopropyl [22], butyl [23], and isobutyl [24]. Our objectives in exploration of novel 2methoxyethyl phenylcyanoacrylates (MEPA) were twofold: (1) to utilize Knoevenagel condensation for synthesis of MEPA compounds with a variety of potentially reactive functional groups and (2) to explore feasibility of radical copolymerization with a commercial monomer styrene.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of the copolymers was kept between 10 and 20% to minimize compositional drift (Table 1). Nitrogen elemental analysis showed that between 23.3 and 41.1 mol% of OPCA is present in the copolymers prepared at ST/ OPCA = 3 (mol), which is indicative of relatively high reactivity of the OPCA monomers towards ST radical which is typical of halogen ring-substituted OPCA [18][19][20][21][22][23][24][25][26][27]. Since OPCA monomers do not homopolymerize, the most likely structure of the copolymers would be isolated OPCA monomer units alternating with short ST sequences (Scheme 2).…”
Section: Synthesis and Characterization Of Styrene -Opca Copolymersmentioning
confidence: 99%
“…Thus, copolymerization of electrophylic TSE monomers having double bonds substituted with halo, cyano, and carbonyl groups and electron-rich monosubstituted ethylenes such as styrene, N-vinylcarbazole, and vinyl acetate [16][17][18] show a tendency toward the formation of alternating copolymers -thus suggesting a way of functionalization of commercial polymers via introduction of isolated monomer units in copolymers. Earlier we have reported synthesis and styrene copolymerization of a number of halogen ring-substituted methyl [19][20][21], ethyl [22], propyl [23], isopropyl [24], butyl [25], isobutyl [26], and 2methoxyethyl [27] PCAs.…”
Section: Introductionmentioning
confidence: 99%